2011
DOI: 10.1111/j.1447-0594.2011.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response of 23‐valent pneumococcal polysaccharide vaccinated elderly and its relation to frailty indices, nutritional status, and serum zinc levels

Abstract: Poor nutritional status, frailty and a lower zinc level impair the immunological response of elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Zn deficiency also predisposed to impaired immune response to Pneumococcal surface protein A, increased nasal S. pneumoniae colonization, and severe pneumococcal infection in mice (133) resulting in shorter survival time after infection (134). correspondingly, patients with better immune response to 23-valent pneumococcal polysaccharide vaccine were characterized by significantly higher serum Zn levels (135). However, no effect (136) or serotype-specific effect (137) of Zn on antibody production in response to polyvalent pneumococcal vaccine was observed.…”
Section: Zinc and S Pneumoniae Infectionmentioning
confidence: 99%
“…Zn deficiency also predisposed to impaired immune response to Pneumococcal surface protein A, increased nasal S. pneumoniae colonization, and severe pneumococcal infection in mice (133) resulting in shorter survival time after infection (134). correspondingly, patients with better immune response to 23-valent pneumococcal polysaccharide vaccine were characterized by significantly higher serum Zn levels (135). However, no effect (136) or serotype-specific effect (137) of Zn on antibody production in response to polyvalent pneumococcal vaccine was observed.…”
Section: Zinc and S Pneumoniae Infectionmentioning
confidence: 99%
“…On the other hand, 4 wk after vaccination with the 23-valent pneumococcal polysaccharide vaccine, elderly individuals with a 10% increase in immunoglobulin M (IgM) memory B cells showed higher serum Zn levels compared to those with an immune response <10% of increase in IgM memory B cells (12). It has been suggested that Zn supplementation may influence the antibody response to immunization, even in those individuals presenting normal Zn plasma levels prior to the supplementation (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, on HIV-positive and in drug addict subjects, Zn supplementation (300 mg/day for 6 days) did not affect the immune response to the 7-valent pneumococcal conjugate vaccine (11). On the other hand, Zn serum deficiency impaired the immune response of 23-valent pneumococcal polysaccharide vaccine, analyzed by the level of immunoglobulin M memory B cell before and 4 wk after vaccination in elderly individuals (12).…”
Section: Introductionmentioning
confidence: 99%
“…45 Next, the likelihood of confounding due to nutritional status, organ function, or subsequent medications upon immune response was not addressed. 46 This is because the sample size was too small to permit the use of a multivariable regression model. 47 These co-morbid factors may confound any association between host immunity and survival, and would be expected to result in bias away from the null.…”
Section: Discussionmentioning
confidence: 99%